Dry eye disease, a prominent manifestation of systemic autoimmune disorders. Issue 6 (November 2022) - Bustamante-Arias, Andres; Ruiz Lozano, Raul E.; Rodriguez-Garcia, Alejandro
Objectives: Dry eye disease (DED) is arguably the most frequent ocular disease encountered in ophthalmic clinical practice. DED is frequently an underestimated condition causing a significant impact on visual function and quality of life. Many systemic autoimmune diseases (SAIDs) are related to moderate to severe DED. The main objective of this review is to enhance the awareness among ophthalmologists of the potential association of an underlying SAID in a high-risk patient with DED. Methods: An exhaustive literature search was performed in the National Library of Medicine's Pubmed, Scopus, Web of Science, and Google Scholar databases for all English language articles published until November 2021. The main keywords included "dry eye disease" associated with autoimmune, connective tissue, endocrine, gastrointestinal, hematopoietic, vascular, and pulmonary diseases. Case reports, series, letters to the editor, reviews, and original articles were included. Results: Although DED is frequently associated with SAIDs, its diagnosis is commonly delayed or missed, producing significant complications, including corneal ulceration, melting, scleritis, uveitis, and optic neuritis resulting in severe complications detrimental to visual function and quality of life. SAID should be suspected in a woman, 30 to 60 years old with a family history of autoimmunity, presenting with DED symptoms and extraocular manifestations including arthralgias, dry mouth, unexplained weight and hair loss, chronic fatigue, heat or cold intolerance, insomnia, and mood disorders. Conclusions: Establishing the correct diagnosis and treatment of DED associated with SAIDs is crucial to avoid its significant burden and severe ocular complications.